2016
DOI: 10.1002/admi.201500646
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal, Biomaterial‐Focused Anticoagulation via Superlow Fouling Zwitterionic Functional Groups Coupled with Anti‐Platelet Nitric Oxide Release

Abstract: The functions of anti‐fouling, zwitterionic polycarboxybetaine (pCB) coating, and anti‐platelet nitric oxide (NO) release replicate key anticoagulant properties of the endothelium. The two approaches, only tested separately thus far, are paired on gas permeable polydimethylsiloxane (PDMS) membranes and evaluated for fibrinogen (Fg) and platelet adsorption. Uncoated (control) and pCB‐coated PDMS separate sheep plasma (108 platelets per milliliter) and gas flow chambers within bioreactors used in this study, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 42 publications
1
27
1
Order By: Relevance
“…35, 4161 It is a free radical that reacts with superoxides and oxygen to form peroxynitrite and dinitrogen trioxide, respectively. 42, 43, 62 Nitric oxide’s mechanisms of action against bacteria include nitrosation of amines and thiols in the extracellular matrix, lipid peroxidation and tyrosine nitration in the cell wall, and DNA cleavage in the cellular matrix.…”
Section: Introductionmentioning
confidence: 99%
“…35, 4161 It is a free radical that reacts with superoxides and oxygen to form peroxynitrite and dinitrogen trioxide, respectively. 42, 43, 62 Nitric oxide’s mechanisms of action against bacteria include nitrosation of amines and thiols in the extracellular matrix, lipid peroxidation and tyrosine nitration in the cell wall, and DNA cleavage in the cellular matrix.…”
Section: Introductionmentioning
confidence: 99%
“…However, in addition to the small capillary diameter, interaction of blood components such as platelets with exposed PDMS may cause clogging of the capillaries. Recent developments of antifouling coatings (also dopamine‐based) could help circumventing this issue as these coatings drastically reduce the interactions of blood platelets and fibrinogen and PDMS …”
Section: Discussionmentioning
confidence: 99%
“…Recent developments of antifouling coatings (also dopamine-based) could help circumventing this issue as these coatings drastically reduce the interactions of blood platelets and fibrinogen and PDMS. [54] Alternative applications of this multifunctional device could involve studying the binding interactions of immobilized biomacromolecules such as mucins with a set of smaller test molecules as well as the immobilization of enzymes, thus providing a low-cost stationary phase for performing enzymatic reactions in a laboratory scale without the need of separating the enzymes from the substrates afterward.…”
Section: Wwwadvancedsciencenewscom Wwwmbs-journaldementioning
confidence: 99%
“…Incorporation of hydrophilic functional groups to a polymeric material has, in recent years, been considered an effective method of improving resistance to protein adsorption and reducing the coagulant properties of membranes . Carboxyl and hydroxyl groups are two hydrophilic functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporation of hydrophilic functional groups to a polymeric material has, in recent years, been considered an effective method of improving resistance to protein adsorption and reducing the coagulant properties of membranes. 16,17 Carboxyl and hydroxyl groups are two hydrophilic functional groups. Our previous study 18 demonstrated that introduction of these two functional groups could effectively achieve these two objectives for a biomaterial surface that contacts blood.…”
mentioning
confidence: 99%